2016
DOI: 10.1523/jneurosci.2339-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability of Motor Cortical Activity: Implications for Brain Machine Interfaces and Optimal Feedback Control

Abstract: The human motor system is capable of remarkably precise control of movements-consider the skill of professional baseball pitchers or surgeons. This precise control relies upon stable representations of movements in the brain. Here, we investigated the stability of cortical activity at multiple spatial and temporal scales by recording local field potentials (LFPs) and action potentials (multiunit spikes, MSPs) while two monkeys controlled a cursor either with their hand or directly from the brain using a brain-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 51 publications
8
79
1
Order By: Relevance
“…However, this interpretation has several limitations or other possible explanations: positional effects could be small within the limited range of positions sampled during the Radial 8 Target Task; position-related modulation could be outside the two neural dimensions that affect the decoder 26,27 ; and/or position-related neural modulation could be poorly described by a linear fit. To more thoroughly investigate cursor positional effects without these limitations, we performed a set of experiments where monkeys performed a Random Target Task in which longer target hold epochs occurred across a larger span of the workspace.…”
Section: Resultsmentioning
confidence: 99%
“…However, this interpretation has several limitations or other possible explanations: positional effects could be small within the limited range of positions sampled during the Radial 8 Target Task; position-related modulation could be outside the two neural dimensions that affect the decoder 26,27 ; and/or position-related neural modulation could be poorly described by a linear fit. To more thoroughly investigate cursor positional effects without these limitations, we performed a set of experiments where monkeys performed a Random Target Task in which longer target hold epochs occurred across a larger span of the workspace.…”
Section: Resultsmentioning
confidence: 99%
“…The separation between potent and null spaces was also used by Slutzky and colleagues to investigate the long-term stability of BMIs (Flint et al, 2016). They found that the stability of all recorded neurons was not uniformly necessary to achieve stable BMI control, and showed that neural activity in the potent space was significantly more stable than neural activity in the null space.…”
Section: From Single Neurons To Neural Manifoldsmentioning
confidence: 99%
“…Here, it has direct implications for the design and prospective long-term performance of brain–machine interfaces (BMIs) for the control of motor prosthetics [61,65,71]. The stability of movement representations by individual M1 neurons has therefore been addressed comparatively well, yielding, however, conflicting results.…”
Section: Stability Versus Variability In Motor Cortexmentioning
confidence: 99%
“…Furthermore, the ensemble behaviour–response association during learning of a task stabilized, which led to higher across-session correlations in movement-related single-cell activity with increasing task performance [27,37]. Some of the discrepancies in reported single-cell stability may therefore be owing to different levels of task proficiency (also see [71]) or owing to cell-type biases as a result of different cortical recording depths [16]. …”
Section: Stability Versus Variability In Motor Cortexmentioning
confidence: 99%